Estudo do tunelamento em junções túnel de CoFeB=MgO=CoFeB - Della Pace, Rafael Domingues (2011)
Magnetic tunnel junctions (MTJ) ofCoFeB=MgO=CoFeB and multilayers of (CoFeB=MgO)x3 were produced using the technique of magnetron sputtering, where the insulating film was grown in an atmosphere reactive Ar +O. Multilayers were produced on measures of X-ray difraction and magnetization. Junctions for transport measurements. All curves IxV, nonlinear, were measured at room temperature, and adjustments made using the Simmons model for symmetric barrier. Adjustments were made firt for the positive voltages and then to negative voltages, where the height and thickness of the barrier and the effective area of tunneling was always considered free parameters. Since the effective area of tunneling, much smaller than the area produced during deposition,thus indicating the existence of points where the current tunneling through the barrier,due to fluctuations in the thickness of the insulation. The post was seen exponential growth of the resistance multiplied by the effective area of tunneling as a function of thickness, using only the values calculated from the simulation curves IxV. We also observed the curve of conductance versus voltage, for the investigation of oxidation or not the interface between electrode and barrier, showing that almost 100% of samples of the tunnel junctions was low oxidation of the electrode (positive).